A Comparison of Preprandial Mixed Insulin Given Three Times Daily and Basal-Bolus Insulin Therapy Started Postoperatively on Patients Having Coronary Artery Bypass Graft Surgery - (:unkn) unknown (My University, 2012)
Objective: Insulin therapy initiated after coronary artery bypass graft (CABG) surgery has decreased long-term mortality. The aim was to compare the effectiveness of prandial premixed therapy (PPT) using insulin thrice daily and basal-bolus therapy (BBT) on patients having CABG surgery. Patients and Methods: Thirty-four patients having CABG surgery were included. Fasting blood glucose (FBG), postprandial blood glucose (PPBG), hemoglobin A1c (HbA1c) and hemoglobin levels were determined preoperatively and at the first week postoperatively when the patients were randomized to either PPT or BBT. Initial measurements were repeated at the end of three months. Results: Seventeen patients (F/M:9/8; 61.5±8.5 years) were assigned on a random basis to the mixed insulin arm and 17 patients (F/M:10/7; 57.4±9.2 years) to the basal-bolus arm. FBG, PPBG and HbA1c levels of both groups (7.6±0.8 % vs 6.7±0.5 % in the BBT and 7.3±0.7 % vs 7.3±1.0 % in the PPT group) at the end of the 3 months were not different than at the time of randomization. The percentage of patients reaching HbA1c levels below 6.0%, 6.5% and 7.0% were higher in the BBT group compared to the PPT group. Conclusion: For patients who had undergone CABG surgery, BBT provided more patients with HbA1c levels below the target than did PPT. (Marmara Medical Journal 2012;25:16-9

Amaç: Kalp cerrahisi sonrasında insülin tedavisi verilmesinin uzun dönemde mortalite üzerinde olumlu etkileri gösterilmiştir. Bu çalışmanın amacı kardiyak cerrahi geçirecek diyabetik hastalarda taburculuk sırasında düzenlenen 3 lü karışım insülin ve 4 lü bazal-bolus insülin tedavilerinin etkinliklerinin karşılaştırılmasıdır. Hastalar ve Yöntem: Çalışmaya Kartal Koşuyolu Yüksek İhtisas Eğitim ve Araştırma Hastanesi nde koroner arter bypass cerrahisi geçiren 34 diyabetik hasta dahil edilmiştir. Bu hastaların preoperatif dönemde açlık kan şekeri (AKŞ), tokluk kan şekeri (TKŞ), hemoglobin A1c (HbA1c) değerleri ve hemogramları belirlenmiştir. Postoperative1. haftada (taburculukta) aynı kan tetkikleri tekrarlanmış ve hastalara randomize olarak 3 lü veya 4 lü yoğun insülin tedavisi başlanmıştır. Üç aylık takip süresinin sonunda başlangıçta yapılan ölçümler tekrarlanmıştır. Bulgular: Çalışmaya alınan 17 kişi (61,5±8,5 yıl; K/E:9/8) 3 lü kola (1. Grup), 17 kişi (57,4±9,2; K/E:10/7) ise 4 lü kola (2. Grup) randomize olmuştur. İki grupta da 3. ayın sonundaki AKŞ, TKŞ ve HbA1c değerleri (%7,6±0,8 ile %6,7±0,5 1. grupta ve %7,3±0,7 ile %7,3±1,0 2. grupta) randomizasyon sırasındaki değerlerden farklı değildir. Üçüncü ayın sonunda hedef %6,0, %6,5 ve %7,0 HbA1c değerlerine ulaşan hasta sayısı BBT grubunda PPT grubuna göre daha fazladır. Sonuç: Koroner arter cerrahisi geçiren hastalarda BBT 3. ayın sonunda hedef HbA1c değerlerine ulaşan hasta yüzdesi açısından PPT tedavisinden daha etkilidir. (Marmara Üniversitesi Tıp Fakültesi Dergisi 2012;25:16-9)
Koroner Arter Bypass Cerrahisi Geçirenİnsülin Tedavilerinin Karşılaştırılması Hastalarda 3 lüKarışım ve 4 lü Yoğun
Keywords: Genel ve Dahili Tıp